The New Testament speaks ; v. 3 God's Word for a former generation explained for today's people - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All, 1980)
Contents : v. 3 : Romans - Corinthians.
Brethren writer. Donated by the author.
Keywords: Bible. N.T. -- introductions